CONSERVATIVE MANAGEMENT STRATEGIES FOR CARPAL TUNNEL SYNDROME: A NARRATIVE REVIEW - Wiktoria Auguścik; Katarzyna Bielawska; Aleksandra Tlak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: The most common compressive neuropathy of the upper limb causing pain, paraesthesia and hand dysfunction is carpal tunnel syndrome (CTS). In less advanced stages of the disease, conservative treatment plays a key role as an alternative to surgical treatment or as the first stage of intervention. Objective: The main objective of this review is summarize and properly evaluate current conservative treatment methods for carpal tunnel syndrome and to compare their clinical effectiveness with surgical treatment. Methods: A review of the scientific literature was conducted using the PubMed and ScienceDirect databases for studies published between 2015 and 2024. Review articles, clinical studies and meta-analyses on non-surgical treatment, including immobilisation, physiotherapy, pharmacotherapy and corticosteroid injections, were included. Results: Wrist immobilisation, physiotherapy, pharmacological treatment and corticosteroid injections are the most commonly used conservative methods. In patients with mild or moderate forms of the disease, these methods can significantly reduce symptoms and improve hand function. However, depending on the stage of the disease, the duration of symptoms and comorbidities, their effectiveness varies Conclusions: Conservative treatment is an effective and less invasive option for patients with mild to moderate carpal tunnel syndrome. Individualised therapy based on the severity of clinical symptoms and patient needs, which is in line with current guidelines, achieves the best results.